Tubo-Ovarian ectopic pregnancy: a rare twin ectopic pregnancy - Khan, Niama; Farooq, Neha; khan, Mohsin (Journal of the Pakistan Medical Association, 2024)
The most common twin ectopic pregnancy is heterotopic (1/7000). We are reporting a rare case of twin tubo-ovarian ectopic pregnancy, which was presented in the emergency department of Ayub Teaching Hospital Abbottabad. A 30-year-old female arrived with worsening lower Abdominal pain persisting for three weeks. She also had per-vaginal bleeding with passage of clots 1week ago. Clinical examination revealed a tense abdomen with tenderness in the left iliac fossa. Per-vaginally, there was cervical motion tenderness and fullness in the posterior fornix. Beta HCG level revealed a sub-optimal rise whereas Transabdominal ultrasound showed an echogenic shadow in the left ovary. The uterus appeared normal. On exploratory laparotomy a large left ovarian mass was seen with ruptured chronic right tubal pregnancy with adhesions. On cut-section of the ovary, a small foetus was evident. —Continue